2008
DOI: 10.1111/j.1532-5415.2008.01934.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Effects of Treating Obstructive Sleep Apnea in Alzheimer's Disease: A Randomized Controlled Study

Abstract: OBJECTIVE: To examine whether treatment of obstructive sleep apnea (OSA) with continuous positive airway pressure (CPAP) in patients with Alzheimer's disease (AD) would result in improved cognitive function. DESIGN: Randomized double-blind placebo-controlled trial. Participants were randomized to either therapeutic CPAP for six weeks or placebo CPAP for three weeks followed by therapeutic CPAP for three weeks. SETTING: General clinical research center PARTICIPANTS: 52 men and women with mild-moderate AD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
219
0
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 325 publications
(233 citation statements)
references
References 22 publications
3
219
0
11
Order By: Relevance
“…For example, administration of statins (which reduce peripheral blood cholesterol levels) to healthy middle-aged individuals was associated with a reduced dementia risk in one large-scale prospective cohort study 149 ; statins have also decreased the brain burden of Aβ in experimental models of AD 150 , although the results of most studies of statin treatment in patients with AD have been disappointing 151 . Furthermore, treatment with continuous positive airway pressure for sleep-disordered breathing or OSA might delay the onset of mild cognitive impairment and slow or even improve cognitive decline in patients with AD 120,152,153 . These observations support the view that systemic management of an individual's known comorbidities or risk factors, with the aim of maintaining bodily homeostasis, might help to prevent or slow the progression of AD.…”
Section: Diagnosismentioning
confidence: 99%
“…For example, administration of statins (which reduce peripheral blood cholesterol levels) to healthy middle-aged individuals was associated with a reduced dementia risk in one large-scale prospective cohort study 149 ; statins have also decreased the brain burden of Aβ in experimental models of AD 150 , although the results of most studies of statin treatment in patients with AD have been disappointing 151 . Furthermore, treatment with continuous positive airway pressure for sleep-disordered breathing or OSA might delay the onset of mild cognitive impairment and slow or even improve cognitive decline in patients with AD 120,152,153 . These observations support the view that systemic management of an individual's known comorbidities or risk factors, with the aim of maintaining bodily homeostasis, might help to prevent or slow the progression of AD.…”
Section: Diagnosismentioning
confidence: 99%
“…Furthermore, individuals with sleep apnea had a younger age of MCI or AD onset (Osorio et al, 2015). By contrast, successfully treating sleep disturbance can delay the age of MCI onset (Osorio et al, 2015) and improve cognitive function in AD (Ancoli‐Israel et al, 2008; dos Santos Moraes et al, 2006). Together, these findings indicate that high‐quality sleep can mitigate Alzheimer's disease pathology.…”
Section: Lifestyle Associations and Interventions For Aging And Admentioning
confidence: 99%
“…13 Furthermore, randomized controlled trials have demonstrated that treatment of OSA in AD patients can improve sleep quality as well as cognitive performance. [27][28][29] Although the majority of our patients died soon after their studies were performed, a few subjects (and their caretakers) benefitted from treatment of their SRBD and RBD (example case).…”
Section: Discussionmentioning
confidence: 99%